FROM COLONIAL TO NATIONAL PRIVATE: SHIFTING OWNERSHIP OF MEDINI TEA PLANTATIONS IN KENDAL (1950-1951): Dari Kolonial ke Swasta Nasional: Peralihan Kepemilikan Perkebunan Teh Medini di Kendal (1950-1951) - Nailatul Asna; Ibnu Sodiq (Santhet: (Jurnal Sejarah, Pendidikan Dan Humaniora), 2026)
This study examines the historical background of the transition of ownership of the Medini tea plantation in Kendal in 1950-1951 which occurred in the unstable political and security situation in early post-Independence Indonesia. This study aims to determine (1) how the process of transition of ownership of the Medini tea plantation from Colonial to national private in 1950-1951 (2) the social and economic impact of changes in ownership of the workforce and the surrounding community. This study uses the historical method with a qualitative approach. The initial stage in this research is the heuristic stage which is realized through interviews with related sources, collecting contemporary newspaper archives, and literature studies sourced from books and journals. After the data are obtained, a descriptive analysis is carried out, that is, an analysis that describes an event based on the cause-and-effect relationship of a historical phenomenon in each situation. Analysis of these data obtained from documents, literature studies, and interviews, then compiled in the form of historiography. The results showed that the transfer of ownership of the Medini Tea Plantation after independence had a positive and negative impact on the socio-economic life of the surrounding community. The novelty of this study lies in the study of the history of the process of transfer of ownership of tea plantations Medini in the early post-independence period, which has not been widely studied in previous studies are generally more focused on aspects of tea management.